Analysis of a High-Rise Building Frame Considering Wind Pressure Considering Steel RCC composite structure using ETABS - Mukesh Kumar Chaudhary; Afzal Khan (International Journal of Scientific Research in Civil Engineering, 2021)
Tall structures and innovative architectural designing are now a days on trend. every one want beautifull design with safety parameters in a high rise building. For creating such beautiful structures architects and structural engineers always keep safety and structural stability first to avoid any hazadious situation or collapse of structure. Thus in this study we are presenting a technique of structure where we can consider both safety as well as innovative design. As we all known that composite structures are now a days In trend to enhance structural strength and stability therefore in this present work we are considering a symmetrical building frame of G+10 and assigning lateral load i.e. wind load for a selected region of wind speed 39 m/s. I this study we are considering two cases RCC building and Composite structure and comparing both in terms of forces, displacement, moment and cost effectiveness using analysis tool ETABS. In this study it is concluded that composite structure is relatively more stable and economical than RCC structure as it resist 30% more forces and displacement.